The perception of sacred trees as proponent of water spring in Malang Regency East Java, Indonesia - Batoro, Jati; Hakim, Luchman; Rahardi, Brian (Asian Journal of Medical and Biological Research, 2020)
A spring is a place where water comes out of the ground seepage, seeps into the soil, then flows through cracks, gaps or natural tracts. Springs (sumber, tuk, umbulan, belik) are used to extract water by local people. This study was aimed at uncovering the knowledge about the types of sacred trees which supported the traditional conservation for water spring in Malang regency. The survey was carried out directly by taking three specimens in the spring environment. Interviews were conducted in person, in-depth, semi-structurally to the local community and tribe leaders. This study contained also the description of the diversity of sacred tree species which supported water spring in Malang Regency, East Java. The results of the study recorded 41 types of 27 genera and 20 families. The diversity of sacred tree species that are believed to be sacred include: ringin (Ficusbenyamina), lo (Ficusglomerata), serut (Streblusasper), ipik-ipik (Ficusprocera), ilat-ilat (Ficuscallosa), bendo (Artocarpuselastica), jambuklampokwatu (Syzygiumlittorale), aren (Arengapinnata), gayam (Inocarpusfagifer), cangkring (Erythrinafusca). The types of water spring supporter are: bambuori (Bambusablumeana), bambubetung (Dendrocalamusasper), bambuapus (Gigantochloaapus), and of the familiaApocynaceae (Ervatamiasphaerocarpa), kecrutan (Spathodeacampanulata), warugunung (Hibiscus similis) etc. The existence of those meaningful trees is a symbol of the existence of a spring and the start of sustainable culture and customs in Malang Raya. Thus, petrenneeds to get the recognition as a longer, traditional conservation model from the government especially from the local government in a form of village regulation. Preserving the springs and environment is a local wisdom of the people of Malang regency, in an effort to preserve traditional conservation and harmony with the lives of other organisms. Asian J. Med. Biol. Res. September 2020, 6(3): 425-430